Increasing the medico-economic efficiency of preventive counseling for patients with arterial hypertension and behavioral risk factors for non-communicable diseases - O. L. Zadvornaya; A. N. Pishchita (Фармакоэкономика, 2021)
Objective: to evaluate behavioral risk factors (BRF) in patients with arterial hypertension (AH) and to determine the ways of improvement of the approaches to preventive consulting targeted to increase medico-economic efficiency of the prevention of cardiovascular diseases (CVDs).Material and methods. A total of 107 patients aged 40–60 years old that attended health-promoting schools for patients with AH at the institutions of primary medical help in Moscow in 2017–2019 were surveyed. The authors used diagnostic criteria of the risk factors for noncommunicable diseases that have behavioral character according to the classification of the World Health Organization (WHO). Along with that, the authors reviewed the opinion of 128 top managers of the institutions of primary medical help that attended the courses of their qualification improvement “Organization of public healthcare” in 2019. The course was dedicated to the possible ways of improvement of preventive consulting of patients with AH and BRF. The methods of content analysis, synthesis, statistical analysis, comparison, etc. were applied. The authors analyzed the documentation on the prevention of CVDs, scientific publications on the subject from eLibrary, Cochrane Library, PubMed, Scopus databases, and official sites of biomedical journals.Results. The sociological survey revealed data on the presence of BRF of non-communicable diseases in patients aged 40–60 years old with verified AH based on scientifically proven criteria and WHO classification. These criteria allowed to evaluate the degree of the proneness of patients with AH to the influence of harmful risk factors (smoking, alcohol consumption, lack of physical activity, unhealthy eating habits) and their combinations. The sociological survey data obtained from the top management of institutions of primary medical help indicated the necessity of the improvement of approaches to group preventive consulting of patients with AH and BRF.Conclusion. The results of the study revealed the main areas of the systemic mistakes in the preventive consulting of patients with AH that have BRF, associated with the evaluation of individual-psychological peculiarities of a personality, and in the organizational aspects of preventive counseling.